2019
DOI: 10.1371/journal.pone.0217396
|View full text |Cite
|
Sign up to set email alerts
|

Postcoital bleeding is a predictor for cervical dysplasia

Abstract: Background Postcoital bleeding (PCB) is a common gynecological symptom that may cause concern among both patients and physicians. Current literature is inconclusive regarding management recommendations. Objective To identify risk-factors for dysplasia/cancer among patients presenting post-coital bleeding (PCB). Methods Using large health maintenance organization (HMO) database, all women reporting PCB in 2012–2015 were identified. PCB patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…La sinusorragia podría servir como una señal de alarma para las mujeres y los profesionales de la salud, lo que podría llevar a una evaluación más temprana y potencialmente a un diagnóstico y tratamiento oportuno. Así mismo, nuestro estudio respalda la sugerencia de Cohen et al (14) de que el sangrado poscoital está asociado con un mayor riesgo de lesiones cervicales y cáncer de cuello uterino, ya que las pacientes que presentaron sangrado poscoital tenían mayor predisposición a esas patologías en mención en comparación con los controles (OR 1,82, IC 95% 1,02-3,33).…”
Section: Resultsunclassified
“…La sinusorragia podría servir como una señal de alarma para las mujeres y los profesionales de la salud, lo que podría llevar a una evaluación más temprana y potencialmente a un diagnóstico y tratamiento oportuno. Así mismo, nuestro estudio respalda la sugerencia de Cohen et al (14) de que el sangrado poscoital está asociado con un mayor riesgo de lesiones cervicales y cáncer de cuello uterino, ya que las pacientes que presentaron sangrado poscoital tenían mayor predisposición a esas patologías en mención en comparación con los controles (OR 1,82, IC 95% 1,02-3,33).…”
Section: Resultsunclassified
“…Therefore, they suggested that these women could avoid colposcopy unless cervical cancer is clinically suspected. On the other hand, Cohen et al 21 reported that compared with controls, women with postcoital bleeding were significantly more likely to have CIN 1 or higher-grade pathology (odds ratio = 1.82, 95% CI = 1.02–3.33, p = .04). Importantly, only half of the women in our study who presented with postcoital bleeding had performed a Pap smear before pregnancy and none of them had been vaccinated against HPV.…”
Section: Discussionmentioning
confidence: 99%
“…Aetiologies of bleeding were identified as ectropion in 36% and polyps in 3.6%, similar to previously published rates of ectropion in 2–34%, polyps in 4–15%, cervicitis in 33%, and no cause identified in >50%. 6 , 7 , 8 , 10 , 11 , 12 The NCSP and Royal Australian and New Zealand College of Obstetricians and Gynaecologists recommend GPs investigate symptomatic patients for reversible causes. 13 Despite this, 41% (46/112) overall and 32% under age 25 did not have pre‐referral chlamydia and gonorrhoea testing.…”
Section: Discussionmentioning
confidence: 99%